2018
DOI: 10.1002/ep.13044
|View full text |Cite
|
Sign up to set email alerts
|

An eco‐friendly approach for copper (II) biosorption on alga Cystoseira indica and its characterization

Abstract: The alga Cystoseira indica was used for copper (II) removal from aqueous solutions. Effects of initial pH, ion concentration, contact time, and different pretreatments on biosorption were investigated. Potentiometric titration, chemical modification, FTIR and ICP analyses were performed to study the biosorption mechanism. Ho's pseudo‐second order model described kinetics data appropriately. Adsorption isotherm was fitted to Langmuir model with the maximum adsorption capacity of 72.1 mg g−1 at pH 4 and 25°C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The negative shift of the peak from 1074 to 1064 cm −1 also indicated the involvement of C–OH. The result agrees with Roozegar and Behnam 45 , and they also found a negative shift of C–OH peak after alage biosorption of copper. The analysis of FTIR showed that the hydroxyl, amine, and carboxyl groups derived from proteins and polysaccharides might be involved in the S. marcescens biosorption of Y(III).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The negative shift of the peak from 1074 to 1064 cm −1 also indicated the involvement of C–OH. The result agrees with Roozegar and Behnam 45 , and they also found a negative shift of C–OH peak after alage biosorption of copper. The analysis of FTIR showed that the hydroxyl, amine, and carboxyl groups derived from proteins and polysaccharides might be involved in the S. marcescens biosorption of Y(III).…”
Section: Resultssupporting
confidence: 91%
“…This peak overlapped stretching vibrations in the hydroxyl (–OH) and amine (–NH) groups derived from sugars and amino acids 43 , 44 . The distinguished asymmetric and symmetric stretching vibration peaks of carboxylate (–COO − ) were evidenced at 1649 and 1403 cm −1 45 . In addition, the peaks recorded at 1243 cm −1 and 1074 cm −1 were the characteristic peaks of carboxyl/carboxylate and stretching vibrations of C–OH, respectively 46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weak band in the region of 1200-800 cm -1 is attributed to C-OH stretching vibrations of carboxylic acids, since the carboxylic group is the most abundant functional group in brown algae due to the presence of alginate polymer. The broad band below 1000 cm -1 results from long alkyl chains [22,23]. Figure 1b shows similar bands for acid-treated biomass but more intense compared to the natural one indica-ting the presence of enhanced quantity of surface functional groups that have high tendency to bind with metal ions and hence, play a vital role in defining the adsorption capacity of an adsorbent.…”
Section: Infrared Spectroscopy Of Biosorbentsmentioning
confidence: 99%